(untitled) (Ustozlar uchun, 2026)
This thesis explores the upcoming changes in English language education, focusing on the shift from traditional classrooms to digital environments. As technology advances, the focus of learning is moving away from strict grammar rules toward real-world communication skills. The research highlights the importance (AI) and mobile applications in providing personalized lessons for students. The study concludes that while technology is powerful tool, the emotional support of a teacher remains essential. The goal of this paper is to provide a roadmap for students and schools to adapt to these modern educational trends.